Institutional Engagement and Its Role in Livelihood Transformation of Tribal Coffee Farmers in Araku Valley - Lalu, Bailupati; Deb, Atanu; Suman, Swati (Indian Journal of Extension Education, 2025)
Institutional engagement plays a critical role in shaping sustainable livelihoods in rural and tribal areas, where access to resources, markets, and services is often limited. The study conducted in 2024-2025 explored the impact of institutional involvement on the livelihood transformation of tribal coffee farmers in Araku Valley, Andhra Pradesh. Adopting an exploratory sequential mixed-method research design, the study surveyed 180 farmers across six villages using structured questionnaires, focus group discussions, and key informant interviews. Data were analyzed using Social Network Analysis (SNA) with UCINET software to map institutional linkages and assess centrality indicators. The findings revealed that the Naandi Foundation was the most influential institutional actor, maintaining strong and consistent linkages across all villages. Villages with higher institutional connectivity, such as Thudumu, Pakanakodi, and Doravalasa, reported significant improvements in income, skill development, gender empowerment, and market access. The convergence of multiple institutions in these areas created synergies that enhanced overall development outcomes. The study highlighted how collaborative institutional ecosystems foster resilience and build local capacity. It demonstrated how inclusive engagement transforms subsistence farming into market-oriented enterprises, providing a scalable model for rural development and emphasizing the importance of institutional coordination for sustainable livelihood outcomes in tribal regions.
Keywords: Araku valley; Coffee farming; Institutional linkage; Social network analysis; Tribal livelihood